Prenatal Maternal Stress Exacerbates Experimental Colitis of Offspring in Adulthood - Sun, Yue; Xie, Runxiang; Li, Lu; Jin, Ge; Zhou, Bingqian; Huang, Huan; Li, Mengfan; Yang, Yunwei; Liu, Xiang; Cao, Xiaocang; Wang, Bangmao; Liu, Wentian; et al. (Frontiers in Immunology, 2021)
The prevalence of inflammatory bowel disease (IBD) is increasing worldwide and correlates with dysregulated immune response because of gut microbiota dysbiosis. Some adverse early life events influence the establishment of the gut microbiota and act as risk factors for IBD. Prenatal maternal stress (PNMS) induces gut dysbiosis and perturbs the neuroimmune network of offspring. In this study, we aimed to investigate whether PNMS increases susceptibility to colitis of offspring in adulthood. The related index was assessed during the weaning period and adulthood. We found that PNMS impaired intestinal epithelial cell proliferation, goblet cell and Paneth cell differentiation, and mucosal barrier function in 3-week-old offspring. PNMS induced low-grade intestinal inflammation, but no signs of microscopic inflammatory changes were observed. Although no pronounced difference PNMS and control offspring was in terms of their overall measures of alpha diversity for gut microbiota, a distinct microbial community changes characterized by increases in Desulfovibrio, Streptococcus, and Enterococcus and decreases in Bifidobacterium and Blautia were induced in the 3-week-old PNMS offspring. Notably, the overgrowth of Desulfovibrio persisted from the weaning period to adulthood, consistent with the results observed by fluorescence in situ hybridization in the colon mucosa. Mechanistically, the fecal microbiota transplantation experiment showed that the gut microbiota from the PNMS group impaired intestinal barrier function and induced low-grade inflammation. The fecal bacterial solution from the PNMS group was more potent than that from the control group in inducing inflammation and gut barrier disruption in CaCo-2 cells. After treatment with TNF-α inhibitor (adalimumab), no statistical difference in indicators of inflammation and intestinal barrier function was observed between the two groups. Finally, exposure to PNMS remarkably increased histopathological parameters and inflammatory cytokine production in a mouse model of experimental colitis in adulthood. These findings suggest that PNMS can inhibit intestinal development, impair barrier function, and cause gut dysbiosis characterized by the persistent overgrowth of Desulfovibrio in the offspring, resulting in exacerbated experimental colitis in adulthood.